A ratiometric fluorescent sensor based on carbon dots for rapid determination of bisulfite in sugar. (30th October 2022) - Peng, Lulin; Yang, Maohua; Zhang, Mei; Jia, Mingyan
Highlights: We developed a ratiometric sensor for HSO3 − using the carbon dots-Cr (VI) system. The sensor was applied to the detection of HSO3 − in real sugar samples. The prepared paper test strip can realize the semi-quantitative detection of HSO3 − . Abstract: Sulfite is widely used in food and drugs as a preservative; however, excessive intake of exogenous sulfite is harmful to human health. Hence, developing effective methods to detect sulfite and its derivatives is vital. Herein, we present a ratiometric fluorescent sensor for bisulfite based on a dual-emission boron-nitrogen double-doped carbon dots (BNCDs)-Cr(VI) system. After adding bisulfite, the fluorescence intensity at 450 nm was significantly enhanced because of the inhibition of the inner filter effect, while the fluorescence emission at 535 nm decreased. A sensor-based method was developed to determine bisulfite with a linearity range of 0 – 10.0 × 10 2 μmol/L and recoveries of 97.33% – 109.00%, achieving the quantitative detection of bisulfite in real sugar samples. Moreover, a paper test strip-based visual measuring system for bisulfite was developed, which realized the rapid and semiquantitative detection of bisulfite.